TINGKAT KECUKUPAN CAIRAN PADA PASIEN GANGGUAN JIWA DI RUMAH SAKIT dr. H. MARZOEKI MAHDI BOGOR - Sujanawan, Mochamad Enra; Riyadi, Hadi (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2014)
The purpose of this study was to measure the fluids adequacy of mental disorder patients. This study was a cross-sectional study at dr. H. Marzoeki Mahdi hospital in Bogor. The number of subjects were 13 mental disorder patients at a condition of calm and willing to collaborate in data collection body weight, height and consumption for three days. Overall fluids requirement of the total subject was 2 376.39±199.80 mL/day. Mean fluid intake from food, drink and metabolic at the patients were 2 530.78±856.02 mL/day. The fluids adequacy of males were 102.83±8:24%, while the females were 116.90±17.80%. Fluids adequacy in patients were 76.92% categorized as enough and 23.08% categorized as excessive.